(3GdLRGAGJ GdVGZWI ai GdYbhO GdEOGQjI (B: s (3OQGSI ebGQfI Hjf GdfXGejf GdeUQi hGdchjJi (B/ s - (3eGLO edai RGjO GdOjMGfis; (3GfhQ GMeO QSdGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3JJfhY GdLRGAGJ GdJi JhbYgG LgI GdEOGQI Ydi GdeJYGbO eYgG eGHjf LRGAGJ eGdjI hEecGfjI aSN GdYbO hCNQi VGZWI hJJejR gPI GdCNjQI HESJgOGagG ELHGQ GdeJYGbO Ydi JfajP GdJRGeI YjfG eY GdEHbGA Ydi GdQGHWI GdJYGbOjI hef Ke ajXd GdeJYGbO eSFhdG CeGe GdEOGQI hJJfhY CTcGd gPI GdELQGAGJ HMSH WHjYI GdYbO agi ai YbO GdGeJjGR JJeKd ai aQV GdMQGSI Ydi GdeQab eMd GdGdJRGes
(3GWQhMI(B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B272-279s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdLRGAGJ GdVGZWIs; (3GdYbhO GdEOGQjIs; (3GdfXGejjf GdeUQi hGdchjJis; (3CfhGY GdLRGAGJ aj GdYbhO GdEOGQjIs; (3GdLRGAGJ GdeGdjIs; (3GdLRGAGJ GdMfGFjIs; (3aQV GdMQGSI Ydi GdeGd GdYGes; (3VeGfGJ GdeJYGbO JLGg SdWI GdEOGQI ai JhbjY GdLRGAGJ GdVGZWIs; (3GdJRGe GdEOGQI HEYPGQ GdeJYGbOs; (3QbGHI GdbVGA Ydi SdWI GdEOGQI ai JhbjY GdLRGAGJ GdVGZWIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes